Influence of Customer, Trust and Quality of Customer Satisfaction in Customer Loyalty at PO Harapan Jaya Jakarta-Magetan Department - Reska Windartiningsih; Resti Hardini; Kumba Digdowiseiso (Politeknik Siber Cerdika Internasional, 2024)
This study aims to analyze the effect of service quality, trust and customer satisfaction on customer loyalty. In this study using primary data obtained from distributing questionnaires to 100 PO Harapan Jaya Bus customers, Jakarta-Magetan Department. This study uses the Multiple Linear Regression method, the results of this study indicate that there is a positive and significant effect on customer loyalty. There is a positive and significant influence between service quality, trust and customer satisfaction on the loyalty of PO Harapan Jaya Bus customers. The existence of a positive and significant influence between service quality, trust and customer satisfaction on customer loyalty of PO Harapan Jaya Bus Jakarta-Magetan Department shows that the better service quality, trust and customer satisfaction possessed by PO Harapan Jaya, the higher customer loyalty. Customer quality, customer trust and satisfaction are important parts to increase customer loyalty.